DFT, PM3, AM1, and MINDO/3 Quantum Mechanical Calculations for Some INHC Cs Symmetry Schiff Bases as Corrosion Inhibitors for Mild Steel - Majed Kubba, Rehab; Kareem Abood, Fatin (Iraqi Journal of Science, 2023)
Density Functional Theory (DFT) at the B3LYP/ 6-311G basis set level andsemiemperical methods (PM3, AM1, and MINDO/3) were performed on six newsubstituted Schiff bases derivatives of INHC (N-(3-(phenylidene-allylidene)isonicotinohydrazide) using Gaussian-03 program. The calculated quantum chemicalparameters correlated to the inhibition efficiency were studied and discussed at theirequilibrium geometry and their correct symmetry (Cs). Comparisons of the order ofinhibition efficiency of the Schiff bases derivatives, and local electrophilic andnucleophilic reactivity have analyzed. Some physical properties also were studiedsuch as heat of formation, total energy and dipole moment...etc. Also vibrationfrequencies and IR absorption intensities were carried out for the calculated Schiffbases molecules.